The future of civil employment relationships - Duraj, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The theme of this article is an attempt to show the future of civil-law employment relations. The author presents the scale and causes of the phenomenon of the spread of civil law forms of employment and self-employment in the market economy, which are increasingly displacing the classic employment relationship. In his opinion, this tendency is permanent and irreversible. In the future, the employment model should be maintained based on the diversity of acceptable employment bases, assuming the freedom of choice of a regime among employment relationship, civil law contracts and self-employment. There is a need to leave the existing employment structure based on the subordinated work criterion under the management of the employer. It is this employment model that must guarantee the widest (fullest) scope of protection, which should compensate the employee for a permanent state of dependence (subordination) on the employer. It is possible to build other civil-law forms of employment around this specific model of employment relationship, to which, to a limited extent, protective labour law provisions should apply. In addition, there is a need to specify in the provisions of the Labour Code the criteria that distinguish the employment relationship from civil law employment relationships, and in particular the employer’s subordination criterion.